Tanggung Jawab Para Pihak Dalam Perjanjian Penyaluran Fasilitas Pinjaman Pada PT. Tanifund Madani Indonesia - Nadia, Fiska; Lestari, Rika; Firmanda, Hengki (Peneliti.net, 2024)
This Research Is About The Position Of The Parties In The Loan Facility Disbursement Agreement At Pt Tanifund Madani Indonesia. The Parties To The Agreement Are The Lender, The Borrower, And The Operator. The Organizer Includes A Clause For The Transfer Of Responsibility Entirely To The Lender. The Position Of The Lender Gets A Weak Position, Because The Organizer Includes The Clauses Of The Agreement. The Content Of The Agreement States That If There Is A Default Of The Borrower, All Risks Including The Risk Of Default Are Fully Borne By The Lender. Form Of Responsibility The Operator May Attempt To Collect The Borrower As A Form Of Implementation Of Its Obligations. However, There Is No Guarantee The Lender's Refund Will Work. The Objectives Of This Thesis Research, Namely: First, To Find Out And Analyze The Position Of The Parties In The Loan Facility Disbursement Agreement At Pt Tanifund Madani Indonesia; And Second, To Find Out The Responsibilities Of The Parties In The Loan Facility Disbursement Agreement At Pt Tanifund Madani Indonesia. This Type Of Research Can Be Classified As Empirical Or Sociological Legal Research, Because In This Study The Author Directly Conducts Research With The Interview Method To Provide A Complete And Clear Picture Of The Problem Under Study.The Conclusion That Can Be Obtained From The Results Of The Study Is First, There Is A Weak Position For Lenders In The Agreement, That All Risks Including The Risk Of Default Are Fully Borne By The Lender. ; Second, The Responsibility Of The Parties In The Loan Facility Disbursement Agreement That The Operator (Pt Tanifund) Uses Credit Scoring. The Organizer Carries Out Borrower Profiling By Looking At The Application Of Lending With The 5c Principle (Character, Capital, Capacity, Condition Of Economic, Collateral). The Debtor Is Proven Not To Meet The Analysis Of Credit, Especially In The Principle Of Character, In Fact The Debtor Is Proven To Be A Drug User And Shows A Bad Character, Mentality And Character, The Principle Of Capacity Or The Ability Of Debtors To Pay Off Loans As Measured By Business Conditions, Income And Turnover Of Debtors Can Be Seen When The Debtor's Income Decreases So That It Is Difficult To Return Funds, The Principle Of Condition Of Economic That Farmers Are Affected By Fruit Caterpillar Pests And Drought. Does Not Meet The Analysis Of Lending Based On The 5c Principle So That The Operator Can Be Responsible To The Lender. Not Finding Good Faith, Pt Tanifund Madani Indonesia Gives Responsibility As A Form Of Awareness Of Having Made A Mistake.